1994
DOI: 10.1111/j.1600-0447.1994.tb01574.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of the Self‐Rating Inventory for Posttraumatic Stress Disorder

Abstract: In this study a newly developed Self-rating Inventory for Posttraumatic Stress Disorder (PTSD) is presented. The instrument consists of 47 items, reflecting DSM-III-R criteria, associated features and items corresponding to the disorder of extreme stress not otherwise specified. All items are phrased in a trauma-independent way and are measured on an intensity scale. The instrument was validated on 76 subjects with war-related trauma and 59 psychiatric outpatients, one third of whom were traumatized. Test-rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 29 publications
2
80
0
1
Order By: Relevance
“…The result of these correlations was consistent with studies of other PTSD scales using similarly constituted subscales [15, 16]. This may not be surprising, as it is known that some PTSD symptoms overlap with those of depression and of anxiety.…”
Section: Discussionsupporting
confidence: 80%
“…The result of these correlations was consistent with studies of other PTSD scales using similarly constituted subscales [15, 16]. This may not be surprising, as it is known that some PTSD symptoms overlap with those of depression and of anxiety.…”
Section: Discussionsupporting
confidence: 80%
“…Healthy male controls (HC) were recruited through advertisement and were matched for age. HC were included if there was no indication for a psychiatric disorder according to the Hopkins symptom checklist (SCL-90) and the Dutch Self Inventory for PTSD (ZIL), 35 and no report of traumatic experiences. All veterans were screened for psychiatric illness and history of drug abuse using the Structured Clinical Interview for DSM IV axis I disorders.…”
Section: Methodsmentioning
confidence: 99%
“…55,56 As a second study limitation, we note that only 54% of the patients invited to participate did so, thereby raising the possibility of bias in that the participants could be either more or less likely to experience psychiatric symptoms. This participation rate exceeds the 50% criterion used in prior analyses of case-fi nding instruments 57 and is greater than some, 43,44 but not all, 45,46 recruitment rates reported in comparable studies validating other screening instruments. Further, our number of completed MINI reference standard interviews (647) is within the range of those performed in similar validation studies (eg, 585 with the PHQ-9, 46 and 965 reported with the GAD-7 scale 45 ).…”
mentioning
confidence: 86%